Discovering the Relative Efficacy of Inhaled Medications for Chronic Obstructive Pulmonary Disease: Multiple Treatment Comparisons - Ying Zhu; Tong Zhang; Haiyan Li; Yang Yang; Qiong Chen; Lei Kong; Bo Tai (Cellular Physiology and Biochemistry, 2017)
Background: Chronic obstructive pulmonary disease (COPD) is managed by three major classes of inhaled medications: inhaled corticosteroids (ICS), long-acting Beta 2-agonist (LABA), long-acting muscarinic antagonist (LAMA). Single inhaled medication is usually replaced by combined inhaled medications for efficacy enhancement. However, this practice should be supported by clinical evidence for large-scale implementations. Methods: The relative efficacy of inhaled medications is determined by three endpoints: changes in the trough forced expiratory volume in 1 second (tFEV1), changes in the St George’s Respiratory Questionnaire (SGRQ) score and the proportion of SGRQ responders which represents a reduction in SGRQ total score at week 24 of ≥4.0. A total of 76 eligible studies were identified in PubMed and Embase. Relevant data were extracted for the purpose of evidence synthesis. Then, raw mean differences (MD) and odds ratios (ORs) were produced by using the network meta-analysis. Results: Patients with ICS + LABA, ICS + LABA + LAMA, LABA, LABA + LAMA, LAMA exhibited significant increases in the tFEV1 compared to those with placebo (P < 0.05). Moreover, patients with ICS + LABA + LAMA exhibited the largest increase in the average tFEV1 and the largest decrease in the average SGRQ scores compared to those with placebo. COPD patients with ICS + LABA + LAMA were far more likely to achieve a significant reduction in the SGRQ scores compared to those with placebo or other inhaled medications (OR > 1). Conclusions: The combined inhaled medication of ICS + LABA + LAMA may be more efficacious than other inhaled medications for COPD patients.